Stress resistance in barley cultivars of various agroecological origin under extreme continental climate conditions - O. A. Yusova; P. N. Nikolaev; Ya. B. Bendina; I. V. Safonova; N. I. Aniskov (Труды по прикладной ботанике, генетике и селекции)
Background. The barley collection at the N.I. Vavilov AllRussian Institute of Plant Genetic Resources (VIR), being the main source of source material for breeding, is insufficiently studied under conditions of extreme continental climate. The purpose of the research was to assess the adaptability of barley cultivars held by VIR to extreme continentality.Material and methods. The research targets were 24 barley cultivars representing various breeding centers and tolerance regions of Russia. The cultivar ‘Omsky 91’ developed at Omsk Agrarian Scientific Center was used as the reference.Results and discussion. According to the genetic profiles for alleles of hordein-coding loci, provided by the Vavilov Institute of General Genetics, more than 70% of the studied barley cultivars (‘Chelyabinsky 99’, ‘Priazovsky 9’, ‘Zadel’, ‘Sokol’, ‘Zernogradsky 584’, ‘Zadonsky 8’, ‘Khadzhibey’, ‘Beatrice’, ‘Knyazhich’, ‘Zevs’, ‘Kazak’) were linear in their hordein-coding loci. The homeostasis of the cultivars, their stability indices and plasticity levels were calculated. Their intensity measures and selection differentials were determined.Conclusion. The adaptability assessment based on the sum of ranks (calculated using the abovementioned adaptability parameters) showed that the monomorphic cultivars ‘Priazovsky 9’ and ‘Chelyabinsky 99’ as well as cv. ‘Severyanin’ (not listed in the State Register for Selection Achievements) were most adapted to extreme continental climate conditions (sums of ranks ranged from 8 to 29). The adaptability of the identified cultivars was confirmed by high-yielding hybrid populations produced from crossing the selected adaptable cv. ‘Chelyabinsky 99’ with cvs. ‘Omsky 91’ and ‘Omsky 95’ released by Omsk Agrarian Scientific Center. The obtained lines demonstrated higher yields than both the mean yield of the parent cultivars (+1.20 t/ha) and the yield of the best parent cultivar (+0.76 t/ha).